Effect of adding sacha inchi (Plukenetia volubilis L.) seeds to a prototype of convenience food draft, on the nutritional composition and sensory acceptance (2016)
ABSTRACT: The polyunsaturated fatty acids of Sacha Inchi seeds are important in the development of food products with healthy and nourishing properties. The aim of this study was to evaluate the effect of Sacha Inchi (Plukenetia volubilis L) on a prototype convenience food. The nutritional composition and sensory acceptance was evaluated using a completely randomized experimental design. Fixed effect-balanced factorial multiple correspondence analyses were used for the different treatments. Four formulations were developed for the prototype type setting (F0, F5, F7.5 and F10) using Sacha Inchi almonds characterized according to their nutritional composition. The fatty acid composition of the total lipids of the seed was determined by gas chromatography. In the food draft type, sensory parameters such as color, odor, flavor and texture in all treatments were evaluated. The results obtained showed a content polyunsaturated fatty acids of 33.74% in the seed. In addition, the acceptance of sensory parameters evaluated by consumers in the draft prototype was greater than 80%. It was observed that lipid content increased up to 3 times and the content of polyunsaturated fatty acids, 4 times in the treatment of F10 with regard to white F0. About 10% almond Sacha Inchi can be effectively incorporated into draft products with suitable timing sensory characteristics and nutritional value, thus, allowing the foods declared under the Colombian law as a high and good source of omega 3.